Effectiveness of different behavioral interventions on gestational weight gain, post-partum weight retention and anthropometric measures in pregnancy: A randomized controlled trial - Vandana Rani; Shabnam Joshi (Tabriz University of Medical Sciences, 2022)
Background: The antenatal and postnatal periods are critical stages in a woman's reproductive life. Many physical changes occur during pregnancy, such as water retention and excessive weight gain. The aim of the present study is to find out the effectiveness of various behavioral interventions during pregnancy to prevent excessive gestational weight gain (GWG) and postpartum weight retention (PPWR). Methods: In this parallel-group randomized controlled trial, 150 pregnant women with singleton pregnancy, aged 20-30 years, body mass index (BMI)≥18.5 kg/m2 and gestational age of less than 16 weeks were randomly allocated into five groups (N=30 in each group): Group A: Control; Group B: Supervised exercise; Group C: Pedometer; Group D: Text message; and Group E: Pedometer plus text message group. Group B received four supervised exercise sessions per month up to delivery; Groups C and E were urged to increase their levels of physical activity, focusing on pedometer-measured step counts of at least 5000-7500 steps per day on seven consecutive days each month. Group E along with group D also received standard SMS messages about physical activity, diet, motivation, and educational-specific topics. Results: The between-group comparisons revealed a statistically significant reduction in PPWR but insignificant difference in GWG. The greatest reduction in PPWR was found in the supervised exercise group (MD=3.25 kg, 95% CI: [1.75, 4.75], P=0.0001 with effect size (η2 )=0.155). Conclusion: The study found that the supervised exercise can be seen as an effective way of improving the physical activity level and reducing excessive PPWR in pregnant women.